Supporting international students through strengthening their social resources. Issue 5 (4th May 2017) - Arthur, Nancy
Abstract : Efforts to recruit international students to higher education must be matched with preparation of the campus community for engaging with this diverse population. The motives of international students for pursuing international studies, including academic and career goals, are facilitated through building strong relationships with members of the host institution. The social integration of international students is important for their academic performance, for building a sense of connection to the destination country, and for supporting career plans post-graduation. Three key social resources for supporting international student transitions include academic faculty, counsellors, and local students. However, these groups need to be prepared to support international students through a high-quality educational experience and through addressing the demands of living and learning in a new cultural and academic environment. Engagement with international students is critical for their success and offers unique relationships to increase the cross-cultural learning of all members of the campus community.